The progress of civilization and the de dicto/de re distinction - Ebner, Maria (Hybris, 2021)
In this paper I present my own argument in support of the thesis that de dicto beliefs are, in at least one sense, more basic than de re beliefs. This argument rests on the fact of the progress of civilization, which appears, as I try to demonstrate, not to be possible without de dicto beliefs constituting a key part of the mental processes of the inventor. My argument is to counterweigh the force of Tyler Burge’s argument for the fundamentality of de re beliefs, leading to the conclusion that beliefs de re are a necessary condition of language understanding and having propositional attitudes at all (Burge 1977, p. 347-348). The first part of the paper is devoted to the examination of the structure of different versions of transcendental arguments – objective and subjective, the second part focuses on an analysis of Burge’s argument from language understanding, while the aim of the third part is to present the Reader with the argument from the progress of civilization. The exposition of the argument is followed by a discussion of certain possible objections which the argument may face.